MoS2(1−x)Se2x Nanobelts for Enhanced Hydrogen Evolution. (10th December 2015) - Yang, Lei; Wang, Wenhui; Fu, Qi; Zhang, Jingyu; Xiang, Bin
Abstract: Molybdenum disulfide (MoS2 ) has attracted considerable attentions in the application of catalysis. However, the chemically inert property of the basal plane in MoS2 retards the catalytic efficiency. Highly exposing active edge sites and optimizing the electronic structure are the two effective ways to improve MoS2 electrocatalytic activity. Here, we report the synthesis of one dimensional (1D) single-crystal MoS2(1−x) Se2x nanobelts with controllable Se and S content, formed by the vertically aligned basal planes perpendicular to the substrate. The top and bottom surfaces of this 1D structure are fully covered by the active edge sites. The single crystalline nanobelt was characterized by high resolution transmission electron microscopy, atomic force microscopy, Raman, photoluminescence and X-ray photoemission spectroscopy. The introduction of Se into MoS2 optimizes the electronic structures of MoS2(1−x) Se2x nanobelts by tuning the oxidation state of Mo. As a result, the enhanced catalytic activity for hydrogen generation was obtained in the 1D MoS2(1−x) Se2x nanobelts (a low onset overpotential of 139 mV at an electrocatalytic current density of 20 mA/cm 2 and a Tafel slope of 65 mV/decade).